Pengaruh Pengeluaran Pemerintah di Sektor Pertanian terhadap Pertumbuhan Ekonomi di Indonesia - Inayah, Ika (Pusat Riset dan Inovasi Nasional, 2023)
As a country with the potential and rich natural resources, agricultural sector in a broad sense is an important sector in driving economic growth in Indonesia. Gross domestic product (GDP) as an indicator of economic growth shows an increasing trend every year in 2011-2019. GDP of agricultural sector has also increased every year. However, government spending in this sector tends to decrease. Therefore, the purpose of this study is to analyze the effect of government spending on agriculture sector on economic growth in Indonesia. This study uses multiple regression analysis with the Ordinary Least Square (OLS) approach using time series data for 2011-2019. Dependent variable is GDP at constant prices and independent variables are government expenditure in the food crops, horticulture, plantation, animal husbandry, agricultural and hunting services, forestry, and fisheries subsectors. The results show that government spending on the food crops, estate crops and fisheries subsectors had a significant and negative effect on Indonesia's GDP at a real level of 5%. The government expenditure in the agriculture and hunting services subsector as well as forestry and logging has a significant and positive effect on Indonesia's GDP.